Researching policy presence and absence: implications and practicalities for urban policy mobilities - Silva, Diogo Gaspar (2023)
Researching comparatively urban policymaking processes has become an ordinary praxis within urban policy mobilities studies. While it has been broadly accepted that thinking through relational dualisms, such as that of policy presence/absence, is useful to examine urban policymaking processes across multiple spatialities and temporalities, less attention has been paid to how we comparatively study such arenas. This article stands as an invitation to reflect on the methodological issues and implications of studying through sites and situations of policy presence and absence within urban policy mobilities. Building on a reflexive learning ontology that emerged out of an academic project that examines the relational and territorial (un)making of Business Improvement Districts across four English town centers, the article discusses how access to, navigation through and thickness of the evidence obtained from the research field is sensitive to the sites and situations of policy presence and absence where the research takes place. It is argued that studying such dissimilar policy arenas should encapsulate flexible research strategies to better attune to the situated processes and politics that engendered such policy outcomes. To address this concern, the article reflects on how positionality, institutional memory and chronopolitics should inform methodological praxis when researching sites and situations of policy presence and absence.